What makes a 'machi' a real 'machi': an exploration of the problem of ritual healing efficacy - Barros Cajdler, A (2020)
This ethnography examines ritual healing transformations in the Mapuche context from the perspective of the phenomenology of the body. It seeks to explore how people know who is a ‘real’ machi or a Mapuche shaman. A real machi can both know or see illness and misfortune and treat them, and make ‘spirits from the past’ present so they can provide a message to a community of people.